Dari Pertunjukan Ke Media: Konvergensi Festival Musik Dalam Merespons Pandemi Covid-19 - Fakhri Zakaria; Gustaf Wijaya (Universitas Gadjah Mada, 2022)
The policy of physical and social restrictions as an action to prevent the spread of COVID-19 has forced the organization of music festivals to shift from conventional formats to virtual stages. However, this new format encountered several challenges, from infrastructure to social aspects. The practice of convergence, apart from being a form of adaptation, can also form a new social community that becomes social capital in the sustainability of the music festival, both economically and socially. This paper discusses the adaptation of music performance business actors through the convergence of music performance formats during the COVID-19 pandemic. The research method utilized is a case study. The object of research is Synchronize Fest and Tomorrowland. Both have strong and wide fans social capital. Both also have their unique way in carrying out digital convergence. Synchronize Radio and television broadcasted format is a form of convergence of musical performances carried out by the Synchronize Festival, as previously an annual multi-genre music festival on a national scale. Meanwhile, a multimedia-based website and community activation have become Tomorrowland's way of greeting its fans during the pandemic. This research is a portrait of how music festivals, as one of the sectors affected by the pandemic, are alive and stay connected to their fans.